2021
DOI: 10.21203/rs.3.rs-172573/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Study on Power-Controlled Wire-Arc Additive Manufacturing using a Data-driven Surrogate Model

Abstract: Wire-Arc Additive Manufacturing (WAAM) provides an alternative for the production of various metal products needed in medium to large batch sizes due to its high deposition rates. However, the cyclic heat input in WAAM may cause local overheating. To avoid adverse effects on the performance of the part, interlayer dwelling and active cooling are used, but these measures increase the process time. Alternatively, the temperature during the WAAM process could be controlled by optimizing the welding power. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…In the case of welding, it was demonstrated that the welding sequence of multi-weld bead parts affects the shape and the magnitude of the distortion [7,8]. Similarly, it was shown that part distortion varies significantly in WAAM depending on the deposition pattern, as observed both in experiments [9] and simulations [10][11][12]. Additionally, it was found that the part geometry has a significant impact on the resulting residual stresses and distortions [13].…”
Section: Introductionmentioning
confidence: 81%
“…In the case of welding, it was demonstrated that the welding sequence of multi-weld bead parts affects the shape and the magnitude of the distortion [7,8]. Similarly, it was shown that part distortion varies significantly in WAAM depending on the deposition pattern, as observed both in experiments [9] and simulations [10][11][12]. Additionally, it was found that the part geometry has a significant impact on the resulting residual stresses and distortions [13].…”
Section: Introductionmentioning
confidence: 81%
“…Generally, the sum of the heat fraction, f, between the heat deposited in the front, af, and the rear, ar, regions is equal to two [24]. The model parameters are gathered in Table 1.…”
Section: Goldak Modelmentioning
confidence: 99%
“…The majority of simulation studies were conducted on single-seam wall geometries with a focus on heat source design (Montevecchi et al , 2016; Peyre et al , 2008) and model validation (Peyre et al , 2008; Oyama et al , 2019; Graf et al , 2018 ; Ding et al , 2011). Investigations on more complex and voluminous parts, in which the influence of the welding sequence is more pronounced, were conducted by Israr et al (2018) in a purely simulative comparison study and by Baehr et al (2021) using a temperature-based optimization approach.…”
Section: Introductionmentioning
confidence: 99%